Deformation mechanism and in-situ TEM compression behavior of TB8 β titanium alloy with gradient structure. (10th September 2021) - Liu, Dan; Liu, Daoxin; Cui, Junfeng; Xu, Xingchen; Fan, Kaifa; Ma, Amin; He, Yuting; Bagherifard, Sara
Graphical abstract: Highlights: A gradient structure was fabricated on the surface of TB8 alloy. Mechanics behavior of submicron sized pillars extracted from treated TB8 was studied. The fundamental mechanism behind grain refinement subjected to USRP was investigated. High energy and strain drove an amorphous structure during USRP processing. Abstract: Severe plastic deformation is known to induce grain refinement and gradient structure on metals' surfaces and improve their mechanical properties. However, the fundamental mechanisms behind the grain refinement and micromechanical properties of materials subjected to severe plastic deformation are not still well studied. Here, ultrasonic surface rolling process (USRP) was used to create a gradient microstructure, consisting of amorphous, equiaxed nano-grained, nano-laminated, ultrafine laminated and ultrafine grained structure on the surface of TB8 β titanium alloy. High energy and strain drove element co-segregation on sample surface leading to an amorphous structure during USRP processing. In situ transmission electron microscope compression tests were performed in the submicron sized pillar extracted from gradient structure and coarse grain, in order to reveal the micromechanics behavior of different grain morphologies. The ultrafine grained layer exhibited the lowest yield stress in comparison with single crystal and amorphous-nanocrystalline layers; the ultrafine grained layer and single crystal had an excellent strain hardening rate. The discrepancy among the grain sizes and activated dislocation sources led to the above mentioned different properties. Dislocation activities were observed in both compression test and microstructure evolution of USRP-treated TB8 alloy. An evolution of dislocation tangles and dislocation walls into low angle grain boundaries and subsequent high angle grain boundaries caused the grain refinement, where twinning could not be found and no phase transformation occurred.